The relationship between perineal trauma and postpartum psychological outcomes: a secondary analysis of a population-based survey - Charles Opondo; Siân Harrison; Julia Sanders; Maria A. Quigley; Fiona Alderdice (BMC, 2023)
Abstract Background Perineal trauma, involving either naturally occurring tears or episiotomy, is common during childbirth but little is known about its psychological impact. This study aimed to determine the associations between childbirth related perineal trauma and psychological outcomes reported by women three months after giving birth and to explore factors that could mediate relationships between perineal trauma and maternal psychological outcomes. Methods This study was a secondary analysis of data from a cross-sectional population-based survey of maternal and infant health. A total of 4,578 women responded to the survey, of which 3,307 had a vaginal birth and were eligible for inclusion into the analysis. Symptoms of depression, anxiety, and post-traumatic stress (PTS) symptoms were assessed using validated self- report measures. Physical symptoms were derived from a checklist and combined to produce a composite physical symptoms score. Regression models were fitted to explore the associations. Results Nearly three quarters of women experienced some degree of perineal trauma. Women who experienced perineal trauma reported having more postnatal physical symptoms (adjusted proportional odds ratio 1.47, 95%CI 1.38 to 1.57, p-value < 0.001), were more likely to report PTS symptoms (adjusted OR 1.19, 95%CI 1.04 to 1.36, p-value 0.010), and there was strong evidence that each unit increase in the physical symptoms score was associated with between 38 and 90% increased adjusted odds of adverse psychological symptoms. There was no evidence of association between perineal trauma and satisfaction with postnatal care, although there was strong evidence that satisfaction with labour and birth was associated with 16% reduced adjusted odds of depression and 30% reduced adjusted odds of PTS symptoms. Conclusions Women who experienced perineal trauma were more likely to experience physical symptoms, and the more physical symptoms a woman experienced the more likely she was to report having postnatal depression, anxiety and PTS symptoms. There was some evidence of a direct association between perineal trauma and PTS symptoms but no evidence of a direct association between perineal trauma and depression or anxiety. Assessment and management of physical symptoms in the postnatal period may play an important role in reducing both physical and psychological postnatal morbidity.